2008
DOI: 10.1364/josab.25.000668
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic realization of anisotropic depolarizing quantum channels

Abstract: We employed an electrically-driven polarization controller to implement anisotropic depolarizing quantum channels for the polarization state of single photons. The channels were characterized by means of ancilla-assisted quantum process tomography using polarization-entangled photons generated in the process of spontaneous parametric down-conversion. The demonstrated depolarization method offers good repeatability, low cost, and compatibility with fiber-optic setups. It does not perturb the modal structure of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Maximizing f N (ϕ) yields N opt = −1/ ln λ ⊥ N opt (rounded to the nearest integer and using natural logarithm). This approximation to the optimal "sampling time" N opt only depends on λ ⊥ , which is experimentally accessible through process tomography [40].…”
Section: B Optimal "Sampling Time"mentioning
confidence: 99%
“…Maximizing f N (ϕ) yields N opt = −1/ ln λ ⊥ N opt (rounded to the nearest integer and using natural logarithm). This approximation to the optimal "sampling time" N opt only depends on λ ⊥ , which is experimentally accessible through process tomography [40].…”
Section: B Optimal "Sampling Time"mentioning
confidence: 99%
“…We note that QST is an established experimental tool-in particular in quantum information-inspired setups. It has been used to characterize quantum states in a large number of different platforms- [4][5][6][7][8][9][10][11][12] are an incomplete list.…”
Section: Introductionmentioning
confidence: 99%
“…2. The requirement that the process matrix should have eigenvalues between 0 and 1, that sum up to 1, dictates that physically possible radii can not reside in the dark green zones [9,15]. By examining the parameter space of θ 1 and θ 2 it can be shown that our configuration can create any channel within the yellow zone.…”
mentioning
confidence: 99%
“…In order to study the effect of noise on quantum information channels, there is a need for a physical realization of controlled depolarization processes. Previously, photonic noisy channels which partially depolarize light were implemented in several ways [6][7][8][9][10][11]. Here, we report on the implementation of a simple controllable isotropic depolarizer, which depolarizes to the same extent light of any initial polarization, to any required final degree of polarization.…”
mentioning
confidence: 99%